Challenges of Central Bank Digital Currency Implementation: A Review of Literature - Niroula, Anil; Hamal, Saday; Gajurel, Ram Prasad; Baral, Arjun Kumar; Adhikari, Shruti (Journal of Management, 2024)
Central Banks across the globe are examining the prospect of their digital currency called central bank digital currency (CBDC). The rise of cryptocurrency and the digitalization of the financial sector have induced countries to conduct extensive research to issue their digital currencies, while few have already issued, and some are undertaking extensive pilot tests of CBDC. In this context, the article has two objectives. First, the paper aims to introduce CBDC as the digital currency issued and regulated by the central banks. The second objective is to investigate the set of articles published on CBDC and digital money to understand their major challenges. This paper reviews the selected literature from 2013 to 2024 from various databases using the keywords: Central Bank Digital Currency, CBDC, Cryptocurrency, and Digital Money. A total of 112 studies were selected in the first stage and after detailed assessment 42 studies were selected for review. The review finds some general as well as country-specific challenges. The different challenges of CBDC issuance and implementation are financial stability, challenges for commercial banks, operational challenges, consumer and merchants’ digital financial literacy, lack of differentiation with existing digital payments, cybersecurity risks, privacy, and regulatory challenges. The study also discusses the future areas of research for CBDC. This paper is a unique attempt to review the literature on eight themes of CBDC challenges.